Experimental and numerical investigation on heat transfer and fluid flow performance of sextant helical baffle heat exchangers. (October 2019) - Cao, Xing; Du, Tingting; Liu, Zhan; Zhai, Hongyan; Duan, Zhenya
Highlights: The plan of a right angle between two straight edges simplifies the manufacturing process of baffle plate. Shell-side fluid flow pattern is more like a spiral one owing to increased baffle numbers. Special overlapped structure between adjacent baffles partly restricts the triangular leakage loss. Effects of incline angle were evaluated on thermal, flow and comprehensive performances. Performances of sextant scheme are better than those of quadrant one. Abstract: As a promising substitute for the segmental ones, the helical baffles have been gradually popularized in shell-and-tube heat exchangers. Quadrant helical baffles are commonly utilized to induce a pseudo-spiral flow pattern in the shell side of helical baffle heat exchangers, but the triangular leakage loss at the conjunction notches between adjacent baffles has always been the bottleneck. An improved scheme of sextant helical baffle is thus presented as a means of leakage blockage in this work. The experimental approach is implemented and the computational model is established for experimental and numerical analysis of the performance of novel heat exchanger, and a good agreement is achieved by comparing measured data with numerical predictions. The modified flow field characteristic of sextant helical baffle heat exchangers (SHBHXs) is examined in detail in comparison with quadrant helical baffle heat exchangers (QHBHXs). It concludes that the reverse flow in the triangular leakage zone is partly dampened by virtue of special overlapped structure of adjacent sextant helical baffles, and shell-side axial velocity exhibits the feature of uniform distribution. The impact of incline angle is particularly evaluated on variations of shell-side heat transfer coefficient and shell-side pressure drop as well as their ratio, and then the relevant correlations for Nusselt number and friction factor are fitted in the calculation scope. Further comparison results reveal that the thermal performance and the comprehensive performance are much better while the pressure drop is much lower in SHBHXs than in QHBHXs, which can be explicated by a finer field synergy property in SHBHXs on the basis of the field synergy theory. This work can provide theoretical foundation for design and optimization of the new type heat exchanger.